A real‐world data of Immune checkpoint inhibitors in solid tumors from India. (16th February 2021) - Noronha, Vanita; Abraham, George; Patil, Vijay; Joshi, Amit; Menon, Nandini; Mahajan, Abhishek; Janu, Amit; Jain, Srushti; Talreja, Vikas T; Kapoor, Akhil; Kumar Singh, Gunjesh; Khaddar, Satvik; et al.
Abstract: Background: Checkpoint inhibitors (Nivolumab and Pembrolizumab) are approved for multiple indications in solid tumors. However access to these therapies is limited in low and middle income countries. Hence we performed an audit to identify accessibility, adverse event rates, compliance, progression free survival and overall survival in solid tumors. Methods: This was a single center retrospective analysis of prospective data base of patients with non‐melanoma solid tumors who were treated with immunotherapy from August 2015 to November 2018. Adverse events during immunotherapy were documented and graded using CTCAE (Common terminology criteria for adverse events), v. 4.02. The response rates to immunotherapy, toxicities and the time to onset and resolution of toxicities were also evaluated as secondary endpoints. Results: Out of 9610 patients, only 155 patients (1.61%) could receive immunotherapy. The most common malignancies included metastatic non‐small cell lung cancer, metastatic renal cell carcinoma, metastatic urothelial carcinoma and relapsed/recurrent head and neck squamous cell carcinoma. Median overall survival in patients who received immunotherapy in non‐melanoma solid malignancies was 5.37 months (95% CI, 3.73–9.73). Poor performance status at baseline was the only adverse prognostic factor. The median progression free survival was 2.57 months (95% CI, 1.73–3.83). Immunotherapy was well tolerated with most common side effects being fatigue 14.8% and anorexia 5.8%. The cumulative incidence of immune related adverse events like hepatitis, pneumonitis, colitis and nephritis was less than 10%. Conclusion: Real‐world data in Indian setting confirms the benefit of immunotherapy in patients with advanced non‐melanoma solid tumors. Abstract : This is the first and largest real world data of immunotherapy from India. It focuses on efficacy and tolerability of immune check point inhibitors in Indian patients.